A fuzzy imperfect production inventory model based on fuzzy differential and fuzzy integral method - Amalesh Kumar Manna; Leopoldo Eduardo Cárdenas-Barrón; Jayanta Kumar Dey; Shyamal Kumar Mondal; Ali Akbar Shaikh; Armando Céspedes-Mota; Gerardo Trevi\~no-Garza (Journal of Risk and Financial Management, 2022)
In the inventory theory, to treat the uncertainty, the fuzzy set concept is used in order to provide a feasible approach to deal with the uncertainty problem. In this research work, a fuzzy economic production quantity model with interactive fuzzy demands is proposed. In a production process, in the beginning, the system is assumed to be in a controlled state in which only perfect items are manufactured. Later, the manufacturing production process shifts to be an out-of-control-state system; producing both perfect and imperfect items simultaneously, this is considered as a fuzzy state. The defective production rate is also taken into account as a fuzzy state. Here, the selection process of produced items is realized during the production period. With the aim of studying the practical feasibility of the fuzzy economic production inventory model along with a sensitivity analysis of some parameters, different numerical examples are illustrated.
Keywords: 650; fuzzy demand; fuzzy economic production quantity; fuzzy imperfect production process; fuzzy integral method; fuzzy programming technique